2009
DOI: 10.1177/0022034509341637
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Force Induces VEGF Production in Periodontal Tissues

Abstract: During orthodontic tooth movement, the activation of the vascular system in the compressed periodontal ligament (PDL) is an indispensable process in tissue remodeling. We hypothesized that compressive force would induce angiogenesis of PDL through the production of vascular endothelial growth factor (VEGF). We examined the localization of VEGF in rat periodontal tissues during experimental tooth movement in vivo, and the effects of continuous compressive force on VEGF production and angiogenic activity in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 25 publications
3
70
0
3
Order By: Relevance
“…However, it is necessary to clarify the significance of growth factor production induced by mechanical stress in hPDL cells in the future. Miyagawa et al [5] reported that compressive forces induce VEGF production in periodontal tissues. Li and colleagues [24] have reported that compressive forces induce FGF-2 expression in periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to clarify the significance of growth factor production induced by mechanical stress in hPDL cells in the future. Miyagawa et al [5] reported that compressive forces induce VEGF production in periodontal tissues. Li and colleagues [24] have reported that compressive forces induce FGF-2 expression in periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in these cytokines expression are involved in PDL remodeling. Furthermore, it has been reported that several types of mechanical force induce the expression or production of growth factors in hPDL cells [5][6][7]. It has been reported that epidermal growth factor increased the number of PDL cells [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF diketahui menjadi faktor angiogenesis diproduksi oleh berbagai jenis sel termasuk fibroblas, sel otot polos, kondrosit hipertrofi, osteoblas dan lain-lain. VEGF immunoreactivity ditemukan dalam sel endotel vaskular, dalam fibroblas yang berdekatan dengan jaringan hialinisasi, sebuah daerah nekrotik di daerah tekanan pada osteoblas, osteoklas, dan sel mononuklear (Miyagawa, 2009).…”
Section: Pengantarunclassified
“…Bone remodelling is a process of both bone resorption on the pressure site and bone formation on the tension site 9. Orthodontic tooth movement can be controlled by the size of the applied force and the biological responses from the PDL .The force applied on the teeth will cause changes in the microenvironment around the PDL due to alterations of blood flow 10 , leading to the secretion of different inflammatory mediators such as cytokines, growth factors, neurotransmitters, colony-stimulating factors, and arachidonic acid metabolites 11 . As a result of these secretions, remodelling of the bone occurs .The most important growth factor is vascular endothelial growth factor (VEGF), this protein is a member of the PDGF/VEGF growth factor family and encodes a protein that is often found as a disulfide linked homodimer.…”
Section: Introductionmentioning
confidence: 99%